Representasi Kemiskinan Dalam Film Parasite (Karya Boong Joon-Ho) - Muhamad Maruli Opradi; Susiyanto; M. Fikri Akbar (STAI Bumi Silampari, 2025)
This study analyzes how the film Parasite depicts structural poverty through the denotative, connotative, and mythical meanings contained in each scene. At the denotative level, the film displays literal visual elements such as the Kim family's subterranean semi-basement, with dim, yellowish lighting, in stark contrast to the Park family's bright, modern, luxurious home. The connotative level reveals symbolic meanings where the semi-basement represents social decline and the vulnerability of the lower class, while the staircase motif connotes a metaphor for fragile social mobility and the cycle of poverty that is difficult to break. At the mythical level, the film dismantles capitalist ideology that naturalizes poverty as a